2021
DOI: 10.2991/assehr.k.210322.146
|View full text |Cite
|
Sign up to set email alerts
|

The Life Quality and Behavioral Stereotypes Concerning the Health of Students of Medical Professions

Abstract: The goal of research consists in the study of correlation between the self-assessment of the life quality and behavioral stereotypes concerning the health of students of medical professions in terms of the structural and functional approach. 652 students of both sexes took part in this study, the sample showed the equal gender and age representation. Within the context of the empirical part of the study, the "MOS SF-36" questionnaire was used for studying the self-assessment of the life quality, for studying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…Based on the values of the skewness of scores (Table 1), the data were normally distributed and converged to their expected values (Hatem et al, 2022). Overall, students’ mental health was more affected than their physical health, in agreement with other studies carried out in similar settings during the pandemic (Qiu et al, 2019; Thomas et al, 2021; Kosilov et al, 2021). In the pre-pandemic period, the MC scores were higher than in this study (Sabbah et al, 2013), which can highlight its impact on medical students’ mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the values of the skewness of scores (Table 1), the data were normally distributed and converged to their expected values (Hatem et al, 2022). Overall, students’ mental health was more affected than their physical health, in agreement with other studies carried out in similar settings during the pandemic (Qiu et al, 2019; Thomas et al, 2021; Kosilov et al, 2021). In the pre-pandemic period, the MC scores were higher than in this study (Sabbah et al, 2013), which can highlight its impact on medical students’ mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Research by Awad et al indicated that the pandemic also negatively affected medical students’ quality of life, especially their mental health [ 22 ]. These findings have also been supported by studies conducted by other researchers under similar conditions [ 23 , 24 , 25 , 26 , 27 ]. According to the WHO, quality of life can be defined as an individual perceiving their life situation in the context of culture and their systems of values and in reference to their goals, expectations, standards and concerns.…”
Section: Introductionsupporting
confidence: 87%